Tran-Radial Percutaneous Coronary Intervention (PCI) is Safe and Alternative to Conventional Trans-Femoral Approach: Our Experiences at Apollo Hospitals Dhaka (Cardiovascular Journal, 2012)
Background: Aim of the study was to assess the safety of the trans-radial Percutaneous coronary  intervention (PCI) than conventional Trans-femoral approach by using either Bare-metal stents  (BMS) and or Drug Eluting Stent (DES) like Sirolimus-eluting or Paclitaxel-eluting stent. Also to  see its safety in regards of procedural time, quick mobilization, less complication and less radiation  exposure.Methods: Total 117 patients were randomized from a total of 538 patients who had PCI at our center  in the quantifying period. Total 130 stent deployed in 117 patients. Among the patients, Male: 100  and Female:17. Mean age were for Male: 55yrs, for Female: 57yrs. Associated Coronary artery  disease (CAD) risk factors were Dyslipidemia, High Blood pressure, Diabetes Mellitus, Positive FH  for CAD and Smoking (all male).  Results: Our study shows 21.7% had trans-radial PCI. Among the study group; 72 (61.5%) were  Dyslipidemic, 75 (64.1%) were hypertensive: 47(40.2%) patients were Diabetic, FH 29 (24.8%) and  33(33%) were all male smoker. Female patients were more obese (BMI M 27: F 29) and developed CAD  in advance age. Common stented territory were LAD 51 (43.6%) followed by RCA 41 (35%) and LCX  27(23%). Average length and diameter of stented vessel were almost same in all territory. Territory  wise multiple or overlapping stenting was done in LAD 3 (6 stents), RCA 1(2stents), LCX 4 (10  stents). Stent used: BMS 37 (28.5%), Sirolimus 41(31.5%), Paclitaxel 27 (21%), Everolimus 22 (16.9%),  Biolimus 2 (1.5%) and Zotarolimus 1(0.75%). Less Procedural time, reduced radiation exposure, no  procedural complication and overall better patient comfort were observed.Conclusion: Our study has revealed that trans-radial PCI is safe with reduced radiation exposure,  quick mobilization of patient and no procedural complication in all the case, indicates it can be done  routinely as an alternative to conventional Trans-femoral approach. DOI: http://dx.doi.org/10.3329/cardio.v5i1.12274 Cardiovasc. j. 2012; 5(1): 57-61